2011
DOI: 10.5402/2011/580704
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Pilot Randomized Placebo-Controlled Trial in Primary and Secondary Raynaud's Phenomenon with St. John's Wort: Detecting Changes in Angiogenic Cytokines When RP Improves

Abstract: Objectives.To perform a 6-week double-blind RCT in Raynaud's phenomenon (RP) comparing the plant extract St. John's Wort (SJW) to placebo. Methods. RP patients having at least 7 attacks per week were stratified by primary and secondary RP and within secondary by systemic sclerosis or other connective tissue disease. Subjects completed a daily standardized diary recording all RP attacks (frequency, duration and severity). Serum levels of 18 inflammatory and angiogenic cytokines were measured pre- and post-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The serum markers ICAM-1, VCAM-1, soluble E-selectin, VEGF, t-PA and endothelin-1 have been shown to be associated with RP (2829–30–31) and were chosen based on an on-going systemic review and previous published data (28, 32), which revealed that these markers did change in longitudinal studies. Few small studies have shown a decrease in these parameters in association with treatment, but larger studies are needed to evaluate their sensitivity to change (28).…”
Section: Discussionmentioning
confidence: 99%
“…The serum markers ICAM-1, VCAM-1, soluble E-selectin, VEGF, t-PA and endothelin-1 have been shown to be associated with RP (2829–30–31) and were chosen based on an on-going systemic review and previous published data (28, 32), which revealed that these markers did change in longitudinal studies. Few small studies have shown a decrease in these parameters in association with treatment, but larger studies are needed to evaluate their sensitivity to change (28).…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid did not help RP and fi sh oil may have some modest benefi t [ 92 , 93 ]. Subsequent to publication of the metaanalysis, a negative trial was published using St. John's wort which was postulated to be benefi cial due to potential properties of the plant that could alter serotonin [ 94 ]. Interestingly RP improved with St. John's wort, but the improvement was even more with placebo.…”
Section: Complementary and Alternative Medicine (Cams)mentioning
confidence: 99%